Hazardous Substance Detection in Water Environments using Neutron Beams: the SABAT Project - Michał SILARSKI (Wykrywanie niebezpiecznych substancji w środowisku wodnym za pomocą wiązek neutronów: projekt SABAT, 2019)
The ever-increasing risk of terrorist attacks is a stimulus for seeking new, more effective danger detection methods. The article describes new methods of detecting hazardous materials based on the interaction between neutrons and matter. The status of the design of the device for detecting hazardous materials in water environments based on these methods, currently in development at the Jagiellonian University (Kraków, Poland), will be presented as well.
Keywords: Wykrywanie niebezpiecznych substancji